PERANAN AIR DAUN SIRIH (Piper betle Linn.) DALAM MENJAGA KUALITAS BENIH SENGON (Paraserianthes falcataria) - Gusrandi, Yoghi; Arlita, Tuti; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aimed to determine the effect of the role water immersion of Piper betle leaf. Protect Paraserianthes falcataria of seed quality and know the best dosage Piper betle leaf soaking in Paraserianthes falcataria maintain quality seed. The research method used in completely randomized design (CRD) with 4 treatments and 4 replications. The treatment consisted of: S0=Paraserianthes falcataria soaking seeds without Piper betle leaves in 1 liter of water; S1=Paraserianthes falcataria soaking seeds with 100 g of Piper betle leaves in 1 liter of water; S2=Paraserianthes falcataria soaking seeds with 200 g of Piper betle leaves in 1 liter of water; S3=Paraserianthes falcataria soaking seeds with 300 g of Piper betle leaves in 1 liter of water. Research has shown that the Paraserianthes falcataria seeds soaking with water immersion Piper betle leaf able to maintain seed quality. Soaking seeds Paraserianthes falcataria with 300 g Piper betle leaves in 1 liter of water is the best treatment against the percentage of seed germination (81%), the rate of seed germination (3.42 days), increasing the height of drill (4.07 cm) and the time of seed germination (81% in 9 days). Keywords : Paraserianthes falcataria, Piper betle Linn., Seed quality.